The mountain between us [videorecording (DVD)] - Elba, Idris; Winslet, Kate; Mulroney, Dermot; Bridges, Beau; Martin, Charles, 1969- (Twentieth Century Fox Home Entertainment, 2017)
Stranded after a tragic plane crash, two strangers must forge a connection to survive the extreme elements of a remote snow covered mountain. When they realize help is not coming, they embark on a perilous journey across the wilderness.